Smart Window / Anis Amirah Jamal, Noor Aida Yeop Sulaiman … [et al.] - Jamal, Anis Amirah; Yeop Sulaiman, Noor Aida; Syed Putra, Sharifah Naziyah (2019)
The Smart Window is a system that to improve the service quality in every hypermarket. By introducing a technology into a window propose, the product is trying to combine the window and the online system to be a systematic shopping system.